Analisis Keuntungan dan Skala Produksi Usahatani Bawang Merah Pada Lahan Sawah Irigasi di Kecamatan Simpang Tiga Kabupaten Pidie - Syafiqur Rahman; M. Nasir Ismail; Teuku Fadhla; Syarifuddin Syarifuddin (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
The aim of the research is to find out how big the profits of shallot farmers' farming in irrigated rice fields are and to find out the scale of production of shallot farming in Simpang Tiga District. The research methodology is "Survey Method" with the "Simple Random Sampling" technique of 36 farmers. Profit analysis method is analyzed using Gross Margin (GM), Gross Ratio (GR), Operating Ratio (OR), Return on Invested Capital (ROIC), and Net Farm Income (NFI) and Production Scale analysis using multiple linear regression analysis with the Cobb-Douglass Production Function Model. The research results show that the profitability value for Net Farm Income (NFI) is IDR 219,444,254 for the Tajuk variety, IDR 158,004,759 for the F1 variety, and IDR 263,795,930 for the Brebes variety. The Return on Invested Capital (ROIC) value for the Tajuk variety is 0.80, the F1 variety is 0.50 and the Brebes variety is 0.85. The Operating Ratio (OR) for the Tajuk variety is 0.57, the F1 variety is 0.74, the Brebes variety is 0.63 and the Gross Ratio (GR) for the Tajuk variety can be 0.42, the F1 variety is 0.53 and the Brebes variety is 0.42 which means that shallot farming in the research area is able to generate profits and is worth pursuing. And based on the return to scale (RTS) analysis of red onion farming in the research area, the result was 1.873 (Table 11), in the RTS analysis it can be said that the production of red onion farming is in a condition where the output scale is increasing (Incresing return to scale), because the sum of the values of the coefficients of production factors are more than one (∑β > 1). This means that by adding a certain amount of input, shallot farming can achieve full efficiency.